Strategi Pembelajaran Guru PAI Dalam Meningkatkan Sikap Kedisiplinan Dan Kecerdasan Spiritual Siswa Di Madrasah Aliyah Swasta Al –Washliyah Indrapura Kecamatan Air Putih Kabupaten Batu Bara - Hasibuan, Dina Juliana Khofifah; Yusman; Siregar, Abdul Rosip; Yusman, Yusman (STAI Tebing Tinggi Deli, 2024)
This study aims to find out about the Learning Strategy of Islamic Education Teachers in Improving Discipline and Spiritual Intelligence of Students at Al-Washliyah Indrapura Private Islamic High School, Air Putih District, Batu Bara Regency. Learning strategy is a learning activity that must be carried out by teachers and students so that learning objectives can be achieved effectively and efficiently. The research method used is qualitative with a descriptive approach, namely Objects, phenomena or Social Problems that are poured into writing that is written in the form of data and facts in the form of words or pictures, not numbers or surveys, questionnaires, etc. Research data were obtained from the results of observations, interviews and documentation. The results of this study indicate that the Learning Strategy of PAI Teachers in Improving Discipline and Spiritual Intelligence of Students at Al-Washliyah Indrapura Private Islamic High School, Air Putih District, Batu Bara Regency, namely by Providing examples first to students about discipline, Directing students on how to behave disciplined at school, Providing advice to students so that they act disciplined and Giving them punishment if they violate the rules that have been made at school.